2005
DOI: 10.1002/jmor.10361
|View full text |Cite
|
Sign up to set email alerts
|

Sperm structure and phylogeny of Astigmata

Abstract: The Astigmata, a large and variable group, is still a subject of taxonomic dispute. Particularly, their origin from ancestors of the lower oribatid mites (e.g., Malaconothroidea) seems well documented by many lines of evidence. The structure of spermatozoa has been successfully applied to phylogenetic investigations in many animal groups. The aim of our study was to provide new data on spermatozoon structure in Astigmata and to consider its appropriateness in phylogenetic studies. The study reveals information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…There are significant variations in both morphometric (Roldan, Gomendio, & Vitullo, ; Soler et al, ; Soler, Sancho et al, ; Tourmente et al, ) and kinematics parameters of spermatozoa (Fitzpatrick et al, ; Tourmente et al, ). In recent decades, sperm characteristics have been successfully used for taxonomic studies in many animal groups including annelids (Ferraguti & Erséus, ; Ferraguti, Erséus, Kaygorodova, & Martin, ), insects (Dias, Oliveira, & Lino‐Neto, ; Jamieson, ), crustaceans (Jamieson), arachnids (Liana & Witaliński, ), amphibians (Selmi, Brizzi, & Bigliardi, ), fishes (Jamieson), birds (Jamieson, ) and mammals (Roldan et al, ; Soler et al, ; Soler, García et al, ). However, it should be borne in mind that similarities have been found in sperm swimming kinematic patterns between distantly related organisms, which cannot be explained solely by phylogenetic relationships (Guasto, Burton, Zimmer, Hosoi, & Stocker, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant variations in both morphometric (Roldan, Gomendio, & Vitullo, ; Soler et al, ; Soler, Sancho et al, ; Tourmente et al, ) and kinematics parameters of spermatozoa (Fitzpatrick et al, ; Tourmente et al, ). In recent decades, sperm characteristics have been successfully used for taxonomic studies in many animal groups including annelids (Ferraguti & Erséus, ; Ferraguti, Erséus, Kaygorodova, & Martin, ), insects (Dias, Oliveira, & Lino‐Neto, ; Jamieson, ), crustaceans (Jamieson), arachnids (Liana & Witaliński, ), amphibians (Selmi, Brizzi, & Bigliardi, ), fishes (Jamieson), birds (Jamieson, ) and mammals (Roldan et al, ; Soler et al, ; Soler, García et al, ). However, it should be borne in mind that similarities have been found in sperm swimming kinematic patterns between distantly related organisms, which cannot be explained solely by phylogenetic relationships (Guasto, Burton, Zimmer, Hosoi, & Stocker, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, sperm characteristics have been successfully used for taxonomic studies in many animal groups including annelids Ferraguti, Erséus, Kaygorodova, & Martin, 1999), insects (Dias, Oliveira, & Lino-Neto, 2013;Jamieson, 1987), crustaceans (Jamieson1991b), arachnids (Liana & Witaliński, 2005), amphibians (Selmi, Brizzi, & Bigliardi, 1997), fishes (Jamieson1991a), birds (Jamieson, 2007) and mammals (Roldan et al, 1992;. However, it should be borne in mind that similarities have been found in sperm swimming kinematic patterns between distantly related organisms, which cannot be explained solely by phylogenetic relationships (Guasto, Burton, Zimmer, Hosoi, & Stocker, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Only one of those was incongruent with the more general hypothesis of OConnor (1984) that Astigmata evolved within some non-basal clade of oribatid mites: Alberti (1991) noted that Astigmata sperm were unlike those of oribatid mites and similar in some ways to those of an endeostigmatid mite. However, Liana and Witalinski (2005) recently considered Astigmata spermatozoa to be so highly modiWed that their ultrastructure could not help in determining the external relationships of the group.…”
Section: Phylogenetic Relationship Of Astigmata and Oribatidamentioning
confidence: 99%
“…In recent years, sperm structure has been successfully applied to taxonomic considerations for many animal groups, e.g., annelids (Jamieson and Rouse, 1989;Ferraguti and Erséus, 1999;, insects, and other arthropods (Alberti and Weinmann, 1985;Jamieson, 1987Jamieson, , 1991bLiana and Witaliń ski, 2005), fish and tetrapods (Jamieson, 1991a(Jamieson, , 1995. Studies of the ultrastructure of sperm and spermatogenesis in Platyhelminthes showed that in this group, spermatozoa also carry strong phylogenetic information and can be useful in establishing a taxonomic system (Hendelberg, 1965(Hendelberg, , 1969(Hendelberg, , 1974(Hendelberg, , 1977(Hendelberg, , 1983(Hendelberg, , 1986Ehlers, 1985;Justine, 1995Justine, , 2001Bâ and Marchand, 1995;Watson and Rohde, 1995;Watson, 1999).…”
mentioning
confidence: 99%